Evolving Burden and Disparities of Fall-Related Mortality in Hypertensive Elderly Adults Across the United States: A 25-Year Epidemiological Perspective - Faiza Ikram (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Falls are a major health concern in older adults and a leading cause of death, particularly among those with hypertension. However, national trends in fall-related mortality with co-existing hypertension remain understudied. This study examines these trends in U.S. adults aged ≥65 from 1999 to 2023. Methods: A retrospective analysis of deaths from 1999-2023 was conducted using the CDC WONDER database. The study population included adults aged ≥65 years, stratified by age group, sex, ethnicity, geographic region, and place of death. Mortality rates were reported as AAMR per 100,000 population, along with 95% confidence intervals (CI). Temporal trends were analyzed using Joinpoint regression to calculate APC and AAPC. Results: Between 1999-2023, falls with co-existing hypertension accounted for 215,214 deaths, often occurring in medical facilities (50.47%), with an overall AAMR of 18.50 with an AAPC of 10.86% (10.27–11.73, p<0.001). he AAMR increases steadily from 2.89 (2.71–3.07) in 1999 to 38.63 (38.09–39.16) in 2023 with two notable surges were observed an initial spike from 1999–2001 (APC: 43.4%, 95% CI: 27.88–57.90, p<0.001) and a second sharp increase from 2018–2021 (APC: 13.6%, 95% CI: 11.26–15.15, p<0.001). Men consistently had higher AAMR than women (20.39 vs. 17.13), with AAPC of 11.24% and 10.57%, respectively. Mortality rates increased across all racial groups, with the highest AAMR in non-Hispanic (NH) White (20.10), Hispanic (13.50), NH Asian or Pacific Islander (12.74), and NH Black or African American (10.38), with corresponding AAPCs of 11.31%, 8.90%, 6.42%, and 7.68%, respectively. Regionally, the Midwest had the highest AAMR (22.88), followed by the West (18.58), South (18.15), and Northeast (14.11). Metropolitan areas had consistently higher AAMRs than nonmetropolitan areas. State-level trends revealed the highest AAMR in Oklahoma and the lowest in Alabama. Conclusion: Fall-related deaths with co-existing hypertension have risen sharply, with notable disparities by sex, race, region, and rurality. Enhancing access to care, particularly in western and rural areas, and implementing targeted prevention programs are vital to reducing mortality rates. Keywords: hypertension, fall, mortality